Adviser, teacher, role model, friend : on being a mentor to students in science and engineering - National Academy of Sciences (U.S.); National Academy of Engineering; Institute of Medicine (U.S.) (Washington, D.C. : National Academy Press, 1997)
"This guide offers helpful advice on how teachers, administrators, and career advisers in science and engineering can become better mentors to their students. It starts with the premise that a successful mentor guides students in a variety of ways: by helping them get the most from their educational experience, by introducing them to and making them comfortable with a specific disciplinary culture, and by offering assistance with the search for suitable employment. Other topics covered in the guide include career planning, time management, writing development, and responsible scientific conduct. Also included is a valuable list of bibliographical and Internet resources on mentoring and related topics."--Amazon.com viewed February 3, 2021
What is a mentor? -- The mentor as faculty adviser -- The mentor as career adviser -- The mentor as skills consultant -- The mentor as role model -- Recommendation : improving the quality of mentoring -- Resources.
Includes bibliographical references (pages 72-77).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Science -- Study and teaching -- Handbooks, manuals, etc; Engineering -- Study and teaching -- Handbooks, manuals, etc; Faculty advisors -- Handbooks, manuals, etc; Mentoring in science -- Handbooks, manuals, etc; Mentoring; Teaching; Engineering -- education; Science -- education; Mentors; Teaching; Sciences -- Étude et enseignement -- Guides, manuels, etc; Ingénierie -- Étude et enseignement -- Guides, manuels, etc; Conseillers des étudiants -- Guides, manuels, etc; Mentorat dans les sciences -- Guides, manuels, etc; Mentorat; Enseignement; teaching; SCIENCE -- Study & Teaching; Teaching; Mentoring; Engineering -- Study and teaching; Faculty advisors; Mentoring in science; Science -- Study and teaching; SCIENCE; ENGINEERING; EDUCATION; HANDBOOKS; Electronic books; Handbook; handbooks; Handbooks and manuals; Handbooks and manuals; Guides et manuels; Manuals (Handbooks)